FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN TENAGA KESEHATAN DI MASA PANDEMI COVID-19 DI RSUD KOTA BAUBAU TAHUN 2020 - Egi Yundar Fajriah; La Ode Muhamad Sety; Jusniar Rusli Afa (Endemis Journal, 2021)
The current spread of the COVID-19 outbreak is so fast, causing the world to be in a state of emergency, so that the World Health Organization or WHO has declared the current status of world health in danger. Health workers as the frontline have a very important role in handling COVID-19, where they are in direct contact with infected patients/people so they are very vulnerable to being exposed and infected by the virus, which causes health workers to experience anxiety. The reason is that health workers experience anxiety because they are afraid of being infected with the virus and spreading it to their families. High anxiety can affect the body's immune system to decrease, so that health workers are more at risk of contracting it. The purpose of this study was to determine the factors related to the anxiety of health workers during the COVID-19 pandemic at the Baubau city regional public hospital . This research method used a quantitative approach with a cross-sectional study design with a population of 274 people using a proportional random sampling technique, amounting to 163 people. Statistical test using the Chi square test. The results showed that there was a relationship between the use of personal protective equipment and anxiety with p value = 0.000 <0.005, there was a relationship between marital status and anxiety with p value = 0.003 <0.005 and there was a relationship between knowledge and anxiety with p value = 0.000 <0.005